Exploring EFL Students’ Views on the Implementation of Think-Pair-Share in Reading Comprehension - Fiqhiyah, Faida Abda; Lestari, Iin Widya; Suwandi, Edi; Wafa, Khoirul (Universitas Sulawesi Barat, 2025)
This study explores EFL students' perceptions and experiences regarding the implementation of the Think-Pair-Share (TPS) strategy to enhance reading comprehension. Recognizing the vital role of reading skills in language development and academic success, the research investigates how TPS facilitates active learning, critical thinking, and collaboration among students. Data were collected through interviews with seven participants and questionnaires from twenty-four students majoring in English Language Education at Nahdlatul Ulama Sunan Giri University during the 2022/2023 academic year. The findings reveal that the majority of students view TPS as a highly effective and enjoyable strategy that improves their understanding of reading texts, builds confidence, and fosters peer interaction. Despite these positive outcomes, students face challenges such as limited time for discussion, difficulty in expressing ideas, and differences in background knowledge, which can hinder discussion quality. The study highlights the importance of teachers considering students' abilities and providing appropriate guidance to maximize the strategy’s benefits. Overall, TPS proves to be a valuable approach in motivating students, increasing their engagement, and improving reading comprehension skills.